2009
DOI: 10.2174/1874914300902010001
|View full text |Cite
|
Sign up to set email alerts
|

Problems and Counselling Needs of Unemployed Youths in Nigeria

Abstract: Unemployment is an issue that has bedeviled Nigeria for quite some time now. Unemployment has a negative multiplier effect not only on the individual involved but on the society as well. Toward this end, this study is designed to explore the problems and counselling needs of unemployed youths in Nigeria. A multi-staged sampling technique was used to select 1,750 unemployed youths from the six geo-political zones of the country including Abuja, the Federal Capital Territory. A research instrument titled "Proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Similarly, Omoniyi (2016) and Omotosho et al (2009) revealed that unemployed youths in Nigeria suffer from an array of problems ranging from health related issues to psychosocial issues. There is no known study that sheds light on the psychological wellbeing of unemployed distinction graduates, which is the main concern of this study.…”
Section: Psychological Wellbeingmentioning
confidence: 99%
“…Similarly, Omoniyi (2016) and Omotosho et al (2009) revealed that unemployed youths in Nigeria suffer from an array of problems ranging from health related issues to psychosocial issues. There is no known study that sheds light on the psychological wellbeing of unemployed distinction graduates, which is the main concern of this study.…”
Section: Psychological Wellbeingmentioning
confidence: 99%
“…This unemployment problem as maintained a steady rise over the years. Nigeria's current economic under-performance is erratic and short of expectations, such that 66% of Nigeria's citizens, educated youths especially, live below the international poverty line, at just $1.00 a day or $300.00 a year (Omotosho, 2009). This is an indication that the Nigeria over the years has gradually disintegrated from its highly buoyant and respected position among developing nations of the south (Obumneke, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria is economically under-productive, relative to its potential for significant development (Omotosho, 2009). From the mid 90's, the employment opportunities in Nigeria has been declining though the economy was still much better compared to the present situation where the country is battling with economic recession as a result of dwindling revenue from the main source of income-petrol.…”
Section: Introductionmentioning
confidence: 99%